Faktor-Faktor Yang Mempengaruhi Minat Untuk Membayar Lebih Pada Produk iPHONE 16 - Aulia, Najwa; B.N, Hanna Anastasya; Yana, Yuli; Putri, Zitta Artamevia (CV. Green Publisher Indonesia, 2025)
This study aims to examine more deeply the factors that influence consumers to be willing to pay more for the iPhone 16. By using qualitative data analysis techniques that are descriptive through in-depth online interviews with three informants who are buyers and users of the iPhone 16, and adhering to Customer Value Theory to help further examine the Willingness To Pay made by consumers on iPhone 16 products. The problem in this study comes from consumers who are willing to pay more for the iPhone 16 even though there is a Domestic Component Level (TKDN) regulation that requires them to make some sacrifices to obtain the product. The results show that consumer purchase decisions with high prices are driven by complex considerations involving functional and symbolic value, risk and benefit perception, brand loyalty, and emotional drive in the context of motivation and loyalty, play complementary roles in shaping consumer decisions and become factors that influence consumers to be willing to pay more for the iPhone 16. These findings reinforce the framework of Customer Value Theory, which states that consumers are willing to pay more if the value they perceive (whether functional, emotional, or symbolic). The managerial implications of this study show that there are aspects that need to be continuously improved in marketing strategies that focus on the functional value of the product, managing risk perceptions, as well as maintaining loyalty and evaluating the customer experience. The advice provided can help Apple and its authorized distributors in developing more efficient strategies to increase Willingness To Pay and maintain iPhone 16 user loyalty.